Quantitative immunoassay of Treponema denticola serovar C in adult periodontitis. - Simonson, L G (1990)
Murine monoclonal antibodies specific for Treponema denticola serovar C were produced and characterized in this study. An immunoassay was then developed by using these monoclonal antibodies, and the T. denticola serovar C antigen content of subgingival plaque was quantitated for samples taken from patients with periodontitis and healthy volunteers. The human subgingival plaque samples were grouped by severity of disease and pocket depth measurements at the collection site. The T. denticola serovar C content per milligram of subgingival plaque from deep pockets (greater than 6 mm) of patients with severe periodontitis was found to be twice that of samples collected from deep pockets (4 to 6 mm) of patients with moderate periodontitis or samples collected from healthy subjects (pocket depth, less than 4 mm).